2016
DOI: 10.3892/mmr.2016.5327
|View full text |Cite
|
Sign up to set email alerts
|

Hsa-miR-495 acts as a tumor suppressor gene in glioma via the negative regulation of MYB

Abstract: MicroRNAs (miRNAs) are small non-coding RNA molecules that regulate gene expression at the post-transcriptional level. Previous studies have reported that there are causative links between the abnormal regulation of miRNAs and cancer development. Hsa‑miR‑495 has previously been demonstrated to be downregulated, and to function as a tumor suppressor, in numerous types of human cancer. However, the function and molecular mechanism of hsa‑miR‑495 in glioma remains unclear. In the current study, the expression and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…For instance, Jiang et al revealed that miR-495 overexpression suppresses osteosarcoma cell proliferation, colony formation, invasion and increased apoptosis in vitro (19). Studies showed that miR-495 upregulation inhibits cell proliferation and invasion and induces a metabolic shift in glioma (42)(43)(44). Formosa et al (36) and Li et al (45) indicated that the restored miR-495 expression attenuates prostate cancer cell growth and metastasis and promotes apoptosis in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Jiang et al revealed that miR-495 overexpression suppresses osteosarcoma cell proliferation, colony formation, invasion and increased apoptosis in vitro (19). Studies showed that miR-495 upregulation inhibits cell proliferation and invasion and induces a metabolic shift in glioma (42)(43)(44). Formosa et al (36) and Li et al (45) indicated that the restored miR-495 expression attenuates prostate cancer cell growth and metastasis and promotes apoptosis in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The following target miR-495 genes have been identified: HMGN5 (19) in osteosarcoma; GFI1 (35) in medulloblastoma; Glut1 (42), MYB (43) and CDK6 (44) in glioma; FZD4 (36), Akt (45) and mTOR (45) in prostate cancer; SATB1 (37) in renal cell carcinoma; STAT-3 (38) and Bmi-1 (39) in breast cancer; epithelial and endothelial tyrosine kinase (40), MTA3 (41) and ATP7A (46) in lung cancer; and PTEN (18) in bladder cancer. In our study, IGF1R was demonstrated to be a direct functional downstream target of miR-495 in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are different views on the role of miR-495 in regulating tumor invasion and migration. It has been reported that miR-495 suppresses the aggressive behaviors of glioma [11], prostate cancer [12] and esophageal squamous cell carcinoma cells [13]. However, in breast [14], bladder [15] and gastric [16] cancer cells, this miRNA promotes tumor invasion and migration.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we found that miR-495 could directly target Annexin A3 in CRC cells using the online database TargetScan 6.2. Currently, miR-495 has attracted much attention because several studies have reported that miR-495 is frequently decreased and functions as a tumor suppressor in gliomas as well as gastric and endometrial cancers [15-17], but it is increased and functions as an oncogene in breast and bladder cancers [18, 19]. However, until now, the level of miR-495 and its the precise mechanism in CRC have been unclear.…”
Section: Introductionmentioning
confidence: 99%